Sustainability in urban logistics: A literature review - Giovanni Garola; Arianna Seghezzi; Chiara Siragusa; Riccardo Mangiaracina (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: The importance of urban logistics is on the rise. On the one hand, the population in cities is growing due to urbanization processes. On the other hand, there is a significant increase in the flow of goods (e.g., a boost in online purchases). Such changes are leading cities to face social, economic, and environmental issues, which urge to be addressed. Based on these premises, this study aims to identify, classify and provide an overview of the environmentally sustainable logistics solutions for urban contexts. Methodology: This study performs a systematic literature review. First, it provides a quantitative description of the results, highlighting eventual trends; second, it displays a narrative description of the papers considered to map the current solution and of the related methodology. Findings: The study highlights the maturity and interest in adopting more sustainable delivery options in urban logistics. The selection of suitable transport means, the engagement of stakeholders, as well as the definition of norms and regulations, emerge as the most discussed and promising solutions. Originality: This study is a first attempt to classify the existing body of knowledge related to urban logistics, analysing contributions based on different axes of classification and highlighting cutting-edge solutions to propose possible research directions.
urn:nbn:de:gbv:830-882.0200755; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; City Logistics